Markers of cardiovascular disease in patients with preeclampsia: a postnatal study. (7th June 2011) - Waring, G J; Waugh, J J S; Smith, M C; Robson, S C; Bell, R; Campbell, F J; Collins, C H
Abstract : Background: Women with preeclampsia (PE) are at increased risk of cardiovascular disease (CVD) in later life. We aimed to ascertain the prevalence of markers of CVD in a cohort of women recently delivered for PE. Methods: Over 18 months all women delivered for PE (sustained blood pressure (BP) ≥140/90 mm Hg + proteinuria (PCR ≥30 or ≥0.3 g/24 h)) were offered postnatal review incorporating CVD risk assessment involving measurement of BP, proteinuria, fasting lipids and 10 year cumulative risk of CVD event (based on QRISK2). QRISK2 scores were compared to population scores (QRISK2/population risk) to give relative risk (RR) Findings 53 of 78 women offered an appointment attended 8–10 weeks after delivery. Mean (SD) age was 30.9 (5.6) years; 70% were primigravida, 87% white, 36% delivered preterm, 60% had family history of CVD (first degree relative), 66% had body mass index >25 and none were current smokers. 32 (60%) had a raised total cholesterol (≥5.0 mmol/l), 21 (40%) had a raised TCl/HDL ratio (≥4.0 mmol/l) and 9 (17%) had raised triglycerides (≥1.7 mmol/l). 14 (26%) screened positive for proteinuria, of these median PCR was 11.5 mg/dl (IQR 7.75–21.25). Median QRISK2 score was 0.4% (IQR 0.20–0.95). Median RR was 1.25 (IQR 1.0–3.0) compared to age-matched population risk. Interpretation: A high proportion of women screened 8–10 weeks after PE have risk factors for CVD. Based on the QRISK2 CVD prediction model a significant number of this group of women have at least a 3-fold higher than expected risk of developing CVD in the next 10 years.